Long‐term research reveals multiple relationships between the abundance and impacts of a non‐native species - David L. Strayer; Christopher T. Solomon; Stuart E. G. Findlay; Emma J. Rosi (Limnology and Oceanography, 2019)
Non‐native species are among the most important drivers of the structure and function of modern ecosystems. The ecological impacts of a non‐native species ought to depend on the size and characteristics of its population, but the exact nature of this population‐impacts relationship is rarely defined. Both the mathematical form of this relationship (e.g., linear, exponential, and threshold) and the attributes of the invading population (e.g., density, biomass, and body size) that most efficiently describe its impacts could vary greatly across invaders, ecosystems, and ecological variables. Knowing the shape of this relationship could improve management and help to infer mechanisms of interaction between the invader and ecosystem. We used a long‐term data set on the invasion of the Hudson River ecosystem by two species of Dreissena (the zebra mussel, Dreissena polymorpha , and the quagga mussel, Dreissena rostriformis ) to explore the shape of the population‐impacts relationship for selected ecological variables, including seston, phytoplankton, and several taxa of zooplankton. Most population‐impacts relationships appeared to follow a negative exponential form, but we also found apparent thresholds and scatterplots for some variables. Including information on the traits of Dreissena (body size and filtration rate) often substantially improved models of impacts. We found only slight evidence that the resistance of the Hudson River ecosystem to the Dreissena invasion might be increasing over time. Our results suggest important refinements to widely used conceptual models of invasive species impact, and indicate that defining the population‐effects relationship will be essential in understanding and managing the impacts of non‐native species.

Crab Burrowing Limits Surface Litter Accumulation in a Temperate Salt Marsh: Implications for Ecosystem Functioning and Connectivity - Jorge L. Gutiérrez; Clive G. Jones; Pablo D. Ribeiro; Stuart E. G. Findlay; Peter M. Groffman (Ecosystems, 2018)

Vegetation of riprapped revetments along the freshwater tidal Hudson River, New York - David L. Strayer; Erik Kiviat; Stuart E. G. Findlay; Nancy Slowik (Aquatic Sciences, 2016)

Urbanization changes the composition and bioavailability of dissolved organic matter in headwater streams - Thomas B. Parr; Christopher S. Cronan; Tsutomu Ohno; Stuart E. G. Findlay; Sean M. C. Smith; Kevin S. Simon (Limnology and Oceanography, 2015)
Population growth in cities has resulted in the rapid expansion of urbanized land. Most research and management of stream ecosystems affected by urban expansion has focused on the maintenance and restoration of biotic communities rather than their basal resources. We examined the potential for urbanization to induce bottom‐up ecosystem effects by looking at its influence on dissolved organic matter (DOM) composition and bioavailability and microbial enzyme activity. We selected 113 headwater streams across a gradient of urbanization in central and southern Maine and used elemental and optical analyses, including parallel factor analysis of excitation‐emission matrices, to characterize DOM composition. Results show that fluorescent and stoichiometric DOM composition changed significantly across the rural to urban gradient. Specifically, the proportion of humic‐like allochthonous DOM decreased while that of more bioavailable autochthonous DOM increased in the more urbanized streams. In laboratory incubations, increased autochthonous DOM was associated with a doubling in the decay rate of dissolved organic carbon as well as increased activity of C‐acquiring enzymes. These results suggest that urbanization replaces upstream humic material with more local sources of DOM that turnover more rapidly and may drive bottom‐up changes in microbial communities and affect the quality and quantity of downstream DOM delivery.

Changes in Nitrogen Cycling Processes Along a Salinity Gradient in Tidal Wetlands of the Hudson River, New York, USA - Robert I. Osborne; Melody J. Bernot; Stuart E. G. Findlay (Wetlands, 2015)

Salinity Effects on Phragmites Decomposition Dynamics Among the Hudson River’s Freshwater Tidal Wetlands - Craig T. Connolly; William V. Sobczak; Stuart E. G. Findlay (Wetlands, 2014)

Response of lotic microbial communities to altered water source and nutritional state in a glaciated alpine floodplain - Remo Freimann; Helmut Bürgmann; Stuart E. G. Findlay; Christopher T. Robinson (Limnology and Oceanography, 2013)
Factors driving bacterial community composition (BCC) and linkages to ecosystem function (EF) are a fundamental interest in microbial ecology. Climate warming is expected to cause a shift from glacial‐ to groundwater‐dominated water sources in alpine catchments due to receding glaciers, which is likely accompanied by a shift in BCC and EF. In this context, we performed a reciprocal transplant experiment of hyporheic sediments within a Swiss alpine floodplain. We assessed the influence of water source (groundwater = krenal, glacial water = kryal) and nutritional state (C, N, and P) on BCC and EF. Experimental response was tested using automated ribosomal intergenic spacer amplification and potential activities of eight different enzymes. BCC from both kryal and krenal systems was highly resistant to changes in water source, yet exhibited pronounced EF flexibility. Major factors determining BCC and EF response were sediment origin followed by seasonal variation in BCC. The gradient in seasonal change in BCC showed different strengths in the two water systems. Krenal BCC was more seasonally stable compared with kryal BCC, although functional plasticity showed the same extent in both. This difference in connectivity between BCC and EF suggests that krenal BCC was dominated by generalists, whereas kryal BCC was dominated by specialists. The weak effect of altered nutritional state on BCC and EF indicates a complex but hierarchically structured relationship among these factors. We conclude that microbial communities in alpine catchments are able to rapidly buffer the effect of shifts in water source on ecosystem functioning.

Littoral‐zone influences on particulate organic matter composition along the freshwater‐tidal Hudson River, New York - Glendon B. Hunsinger; Siddhartha Mitra; Stuart E. G. Findlay; David T. Fischer (Limnology and Oceanography, 2012)
A multi‐tracer approach was applied to particulate organic material (POM) biogeochemistry along a 165‐km transect of the freshwater‐tidal portion of the Hudson River estuary (HRE). Elemental carbon and nitrogen, stable isotopes, chlorophyll a , and lignin phenols were measured monthly at a mid‐estuary station from August to November 2007, and monthly at the same station and 3–5 additional stations in 2008. POM at stations proximal to major tidal wetland and aquatic vegetation (WETAV) zones showed ∼ 2‰ higher carbon isotopic signature of particulate organic carbon ( δ 13 C POC ), ∼ 3‰ higher nitrogen isotopic signature of particulate nitrogen ( δ 15 N PN ), elevated chlorophyll a levels, and up to 3‐fold increases in Λ 8 ‐lignin phenols indicative of relatively fresh plant matter. This prominent shift in POM composition suggests that WETAV areas supply compositionally unique organic matter along the HRE, especially during low flow. Based on shifts in geochemical tracers downstream of the largest WETAV zone, this POM appears to be readily incorporated, metabolized, and/or deposited to bed sediments. Despite representing

Biodiversity in Hudson River shore zones: influence of shoreline type and physical structure - David L. Strayer; Stuart E. G. Findlay; Daniel Miller; Heather M. Malcom; David T. Fischer; Thomas Coote (Aquatic Sciences, 2012)

Effects of Microtopography on Hydrology, Physicochemistry, and Vegetation in a Tidal Swamp of the Hudson River - Jennifer Courtwright; Stuart E. G. Findlay (Wetlands, 2011)

Wetland‐driven shifts in suspended particulate organic matter composition of the Hudson River estuary, New York - Glendon B. Hunsinger; Siddhartha Mitra; Stuart E. G. Findlay; David T. Fischer (Limnology and Oceanography, 2010)
Elemental carbon and nitrogen, stable isotopes, and lignin phenols were quantified for suspended particulate material exchanging between Tivoli Bays wetlands and the main stem of the freshwater‐tidal Hudson River estuary (HRE) across a tidal cycle, seasonally in 2006 and monthly in 2007 during the ice‐free portion of the year. Temporal shifts in organic matter (OM) composition ranged from 33.1 to 247.6 mg g −1 particulate organic carbon (POC), ‐34.7‰ to ‐27.2‰ stable carbon isotopic signature of POC (δ 13 C POC ), ‐3.6‰ to 13.6‰ nitrogen isotopic signature of particulate nitrogen (δ 15 N PN ), and 0.8 to 25.0 mg per 100 mg OC lignin phenols. From May to August, the wetlands transferred abundant (up to 247.6 mg g −1 ), chemically distinctive (δ 13 C POC as depleted as ‐34.7‰) particulate OM to the HRE, particularly Tivoli South Bay. We estimated a net export of > 60 Mg km −2 yr −1 POC from Tivoli Bays into the HRE. Mixing model iterations indicated that planktonic OM was the dominant source (50% to 86%) during summertime, while contributions from allochthonous and planktonic OM during other seasons were roughly equivalent (~ 38%). Taken together, both geochemical data and mixing modeling underscore the function and value of HRE tidal wetlands as major generators of compositionally unique and labile POC for the estuarine carbon budget. In a broader context, lateral aquatic connections with tidal wetlands at seasonal or localized scales may overshadow internal or upland influences on OM composition, production, and processing in estuaries; a latent but key consideration when deciphering temporal and longitudinal trends.

Ecology of freshwater shore zones - David L. Strayer; Stuart E. G. Findlay (Aquatic Sciences, 2010)

Sources of Elevated Chloride in Local Streams: Groundwater and Soils as Potential Reservoirs - Dustin W. Kincaid; Stuart E. G. Findlay (Water, Air, & Soil Pollution, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

The Contribution of Crab Burrow Excavation to Carbon Availability in Surficial Salt-marsh Sediments - Jorge L. Gutiérrez; Clive G. Jones; Peter M. Groffman; Stuart E. G. Findlay; Oscar O. Iribarne; Pablo D. Ribeiro; C. Martín Bruschetti (Ecosystems, 2006)

Multi-Scale Controls on Water Quality Effects of Submerged Aquatic Vegetation in the Tidal Freshwater Hudson River - Stuart E. G. Findlay; William C. Nieder; Elizabeth A. Blair; David T. Fischer (Ecosystems, 2006)

Metabolic and structural response of hyporheic microbial communities to variations in supply of dissolved organic matter - Stuart E. G. Findlay; Robert L. Sinsabaugh; William V. Sobczak; M. Hoostal (Limnology and Oceanography, 2003)
Hyporheic sediment bacterial communities were exposed to dissolved organic matter (DOM) from a variety of sources to assess the interdependence of bacterial metabolism and community composition. Experiments ranged from small‐scale core perfusions with defined compounds (glucose, bovine serum albumin) to mesocosms receiving natural leaf leachate or water from different streams. Response variables included bacterial production, oxygen consumption, extracellular enzyme activity, and community similarity as manifest by changes in banding patterns of randomly amplified polymorphic DNA (RAPD). All DOM manipulations generated responses in at least one metabolic variable. Additions of both labile and recalcitrant materials increased either oxygen consumption, production, or both depending on background DOM. Enzyme activities were affected by both types of carbon addition with largest effects from the labile mixture. Cluster analysis of RAPD data showed strong divergence of communities exposed to labile versus recalcitrant DOM. Additions of leaf leachate to mesocosms representing hyporheic flowpaths caused increases in oxygen consumption and some enzyme activities with weaker effects on production. Community structure was strongly affected; samples from the leachate‐amended mesocosms clustered separately from the control samples. In mesocosms receiving water from streams ranging in DOC (0.5–4.5 mg L −1 ), there were significant differences in bacterial growth, oxygen consumption, and enzyme activities. RAPD analysis showed strongest clustering of samples by stream type with more subtle effects of position along the flowpaths. Responses in community metabolism were always accompanied by shifts in community composition, suggesting carbon supply affects both functional and structural attributes of hyporheic bacterial communities.

Microbial growth and nitrogen retention in litter of Phragmites australis compared to Typha angustifolia - Stuart E. G. Findlay; Susan Dye; Kevin A. Kuehn (Wetlands, 2002)

Catchment-Scale Variation in the Nitrate Concentrations of Groundwater Seeps in the Catskill Mountains, New York, U.S.A. - A. Joshua West; Stuart E. G. Findlay; Douglas A. Burns; Kathleen C. Weathers; Gary M. Lovett (Water, Air, & Soil Pollution, 2001)

Microbial incorporation of nitrogen in stream detritus - Diane M. Sanzone; Jennifer L. Tank; Judy L. Meyer; Patrick J. Mulholland; Stuart E. G. Findlay (Hydrobiologia, 2001)